SWOT Analysis of Ijarah Contracts in the Service Industry: Strategies for Growth and Challenges - Enceng, Enceng Iip Syaripudin; Gaussian, Gini; Burhanudin , Ujang; Becic, Armin (Involvement International Journal of Business, 2025)
The service industry is a critical driver of the global economy, contributing significantly to job creation and quality of life improvement. To remain competitive in an increasingly challenging market, service companies must adopt effective strategies to meet customer expectations. SWOT analysis is a strategic tool that helps businesses identify strengths, weaknesses, opportunities, and threats, making it a valuable approach in this context. This study focuses on applying SWOT analysis to business management in ijarah contracts, a leasing arrangement aligned with sharia principles. The research utilized a qualitative approach, engaging 20 business practitioners in the service industry located in West Java, Indonesia. Data collection methods included in-depth interviews and a comprehensive literature review on ijarah contracts and their application within the service sector. The findings highlight the strengths of ijarah contracts, particularly their compliance with sharia principles and substantial market potential. However, notable weaknesses include limited public understanding of ijarah contracts and the burden of high operational costs. Opportunities such as digitalization and the expanding sharia economy offer significant growth prospects, while threats from conventional financial systems and global economic instability present challenges that require strategic management. The study underscores the importance of addressing operational inefficiencies and enhancing market awareness of ijarah contracts. Furthermore, leveraging digital technology and capitalizing on the growth of the sharia economy can strengthen the position of ijarah-based businesses.